Phylogenetic analysis of dissimilatory Fe(III)-reducing bacteria. - Lonergan, D J (1996)
Evolutionary relationships among strictly anaerobic dissimilatory Fe(III)-reducing bacteria obtained from a diversity of sedimentary environments were examined by phylogenetic analysis of 16S rRNA gene sequences. Members of the genera Geobacter, Desulfuromonas, Pelobacter, and Desulfuromusa formed a monophyletic group within the delta subdivision of the class Proteobacteria. On the basis of their common ancestry and the shared ability to reduce Fe(III) and/or S0, we propose that this group be considered a single family, Geobacteraceae. Bootstrap analysis, characteristic nucleotides, and higher-order secondary structures support the division of Geobacteraceae into two subgroups, designated the Geobacter and Desulfuromonas clusters. The genus Desulfuromusa and Pelobacter acidigallici make up a distinct branch within the Desulfuromonas cluster. Several members of the family Geobacteraceae, none of which reduce sulfate, were found to contain the target sequences of probes that have been previously used to define the distribution of sulfate-reducing bacteria and sulfate-reducing bacterium-like microorganisms. The recent isolations of Fe(III)-reducing microorganisms distributed throughout the domain Bacteria suggest that development of 16S rRNA probes that would specifically target all Fe(III) reducers may not be feasible. However, all of the evidence suggests that if a 16S rRNA sequence falls within the family Geobacteraceae, then the organism has the capacity for Fe(III) reduction. The suggestion, based on geological evidence, that Fe(III) reduction was the first globally significant process for oxidizing organic matter back to carbon dioxide is consistent with the finding that acetate-oxidizing Fe(III) reducers are phylogenetically diverse.